Light-Activated Hydrophobic Adhesive for Shape-Memory Polymer Nerve Cuffs. Issue 1 (2016) - Wobser, Victoria; Yang, Kejia; Modi, Romil; Archer, Wyatt; Patel, Yogi; Voit, Walter
ABSTRACT: In this study, three hydrophobic polymers are investigated as potential adhesives for a shape memory polymer nerve cuff. At room temperature, the adhesive candidate exhibited a maximum lap shear stress of 1.7251 MPa, compared to 0.87641 MPa and 2.1815 MPa for two commercially available biocompatible adhesives.